"Peek-A-Boo, We See You Too": Homelessness and visuality in New York City. (October 2018) - Goldfischer, Eric
This paper examines an anti-homeless visual campaign which appeared in New York City in the summer of 2015, in the midst of a resurgence of public concern over the visibility of homeless New Yorkers. The campaign, produced by a police union and titled "Peek-A-Boo, We See You Too" encouraged police officers and allies concerned with a perceived decline in "quality of life" to photograph homeless people on the street, tagging their locations and uploading the photographs to a website. Using the photographs, concurrent discourses, and evidence from surveys conducted by a homeless-led organization, I argue that this campaign represents more than simply an instance of revenge upon and against the homeless. Rather, I suggest that it represents a moment of what philosopher Kristie Dotson calls "epistemic backgrounding" a case in which the people visually displayed at the center of the pictures are "backgrounded" in the knowledge produced off of their images. Connecting this singular campaign with a broader conception of anti-homeless actions, I suggest that we might understand the relationship of visuality and homelessness as one which relies on revanchism for its political logic but produces the simultaneous absence and presence of homeless people through epistemic backgrounding.